Chlorella vulgaris as a lipid source: Cultivation on air and seawater‐simulating medium in a helicoidal photobioreactor. (8th January 2016) - Frumento, Davide; Aliakbarian, Bahar; Casazza, Alessandro Alberto; Converti, Attilio; Al Arni, Saleh; da Silva, Milena Fernandes
Abstract : The freshwater microalga Chlorella vulgaris was cultured batchwise on the seawater‐simulating Schlösser medium either in a 1.1‐L‐working volume helicoidal photobioreactor (HeP) or Erlenmeyer flask (EF) as control and continuously supplying air as CO2 source. In these systems, maximum biomass concentration reached 1.65 ± 0.17 g L −1 and 1.25 ± 0.06 g L −1, and maximum cell productivity 197.6 ± 20.4 mg L −1 day −1 and 160.8 ± 12.2 mg L −1 day −1, respectively. Compared to the Bold's Basal medium, commonly employed to cultivate this microorganism on a bench‐scale, the Schlösser medium ensured significant increases in all the growth parameters, namely maximum cell concentration (268% in EF and 126% in HeP), maximum biomass productivity (554% in EF and 72% in HeP), average specific growth rate (67% in EF and 42% in HeP), and maximum specific growth rate (233% in EF and 22% in HeP). The lipid fraction of biomass collected at the end of runs was analyzed in terms of both lipid content and fatty acid profile. It was found that the seawater‐simulating medium, despite of a 56–63% reduction of the overall biomass lipid content compared to the Bold's Basal one, led in HeP to significant increases in both the glycerides‐to‐total lipid ratio and polyunsaturated fatty acid content compared to the other conditions taken as an average. These results as a whole suggest that the HeP configuration could be a successful alternative to the present means to cultivate C. vulgaris as a lipid source. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:279–284, 2016